Marketing Management in Eco-Friendly Costume and Carnival Events - Mailina Mailina; Wan Junita Raflah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study analyzes the application of marketing management in organizing the Eco-Friendly Costume Fashion Show and Fashion Carnival at the Polbeng Business Expo, Bengkalis State Polytechnic. The purpose of this study is to describe how marketing management was implemented to increase public awareness and participation while introducing the concept of eco-friendly fashion and promoting local culture. This research used a descriptive qualitative method with a project-based approach. Data were collected through observation, interviews, and documentation involving the organizing committee responsible for planning and implementing the event. The data were analyzed using the Marketing Management System Model, which consists of creating value, communicating value, delivering value, and maintaining participant satisfaction. The results show that the marketing strategies applied during the event helped increase participant registration and attract public attention. The use of social media, promotional posters, brochures, and direct promotion to schools supported the dissemination of information about the event. Good coordination among the organizing committee also contributed to the successful implementation of the program. In addition, the event provided an opportunity to introduce environmentally friendly fashion made from recycled materials while encouraging participants to appreciate creativity and local cultural values. Overall, the study concludes that the application of marketing management contributed to the success of the event, increased community participation, strengthened public awareness of sustainable fashion, supported the achievement of the event objectives, and encouraged the preservation of environmental and cultural values through creative fashion activities.